Interfaces educação especial e fonoaudiologia: um estudo bibliométrico baseado na produção científica de dissertações e teses - Bello, Suzelei Faria (2009)
Speech Pathology and Special Education establish relations of proximity due to similar objects of studies. Besides, the integrated work between professionals maximizes opportunities of growth for both areas. Therefore, the overall objective suggested in this research is to understand how Speech Pathology was taken as the object of research in Special Education based on the analysis of scientific production of dissertations and thesis of the Graduate Program in Special Education of Universidade Federal de São Carlos (PPGEEs/UFSCar). For that reason, the scientific production in Special Education with interface in Speech Pathology was mapped and the main aspects that support such integration were identified. The data source were thesis and dissertations defended in PPGEEs/UFSCar between 1981 and 2005. This program was chosen for being the first and only of the area in the country. The methodological procedures to develop the research involved the following steps: a) review of literature in Special Education and Speech Pathology; b) survey and data collection of dissertations and thesis in Special Education held in PPGEES/UFSCar that had interface with Speech Pathology c) categorization and bibliometric analysis. The results obtained through bibliometric analysis revealed that 74 studies analyzed refer to the interface between Special Education and Speech Pathology; hearing disability was the most investigated; the pieces work were focused on the theme "Teaching and learning" and while conducting a quantitative analysis of the references used on the pieces of work that have the co-relation with the area of Speech Pathology, it was observed that they were indexed in the magazine Pro-fono: Revista de Atualização Científica and in the Journal of Speech and Hearing Disorders; the pieces of work of Special Education in the magazine Revista Brasileira de Educação Especial. Finally, this study aimed to promote the interdisciplinarity between these areas, identified trends and emerging themes that may favor the joint action of these professionals. Moreover, the dissertation aimed to contribute to the construction of a process of reflection and assessment of information produced in Special Education consolidated in scientific production of thesis and dissertations and its interface with Speech Pathology.